PROSES PEMBENTUKAN KATA MAJEMUK DARI KANJI 月(TSUKI ; GETSU ; GATSU) - Yuliana, Riska; rosliana, lina; Ratna, Maharani (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
This research is about the formation process of compound words in which one of thecomponents is kanji 月. Compound words is a word composed of two or more basic words.The aims of this study is to find out the structures that form compound words, to find themeaning of compound words and to find out the syntactic relationship that exists betweenformation words components.The research method which author use in this research is a descriptive method. To writethis thesis, firstly, the author collected the data, analyzed the data and then presented theresult.The result is the 45 data studied is formed based on 5 patterns. The meaning obtained isdivided into two, which are conceptual meaning or literal meaning and associative meaning/indicates a symbolism. Then, there are 8 syntactic relationships that form a compound word.It also found 4 special cases of syntactic relationships.